THE DEVELOPMENT OF AN ATTITUDE SCALE TO MEASURE TEACHERS’ ATTITUDES TO OUT-OF-SCHOOL LEARNING ACTIVITIES (OoSLA): A VALIDITY AND RELIABILITY STUDİES (Third Sector Social Economic Review, 2021)
The present study aimed to develop a scale to measure teachers’ attitudes toward out-of-school learning activities (OoSLA). The study was conducted with 315 teachers via an online survey. Four expert opinions was sought on the content validity of the scale. An Exploratory Factor Analysis (EFA) was performed for the construct validity of the scale. The EFA yielded a structure consisting of 25 items and three factors, which accounted for 58.12% of the variance. The factors that were revealed were labeled as follows: ""To value OoSLA"", ""To attach importance to OoSLA"" and ""Negative Beliefs towards OoSLA"" The reliability of the measurements were determined utilizing the Cronbach Alpha coefficient. Respectively three factor's  and   whole scale Cronbach's alpha coefficients are 89, .90, .87 .92. The item-total correlation and the 27% bottom-top group comparisons showed that all of the items on the scale were discriminatory. Ultimately, the scale reveals teachers'  attitude toward OoSL that gives valid and reliable measurements was obtained.
Keywords: Out-of-school Learning; Attitude; Informal Learning; Non-Formal Learning